A HUMANE APPROACH IN DEALING WITH CHILDREN IN CONFLICT WITH THE LAW - Bernadeta Resti Nurhayati; Samantha Elisabeth C (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2024)
Children are the future of the nation, therefore, they need care, education and guidance from their parents, guardians or foster parents. Their life, however, sometimes doesn't go as expected. Some of them even have to deal with the law because of their unexpected behavior. The future of the children of criminals deserves attention, especially if they have to be responsible for their actions. A humane approach in resolving the cases of children in conflict with the law considers that the children's rights are human rights. They who are in conflict with the law are still given the opportunity to improve themselves and obtain their rights as children.This paper aims to analyze a humane approach as a consideration in implementing diversion. It uses socio-legal method and qualitative analysis based on primary and secondary data. The humane approach views children as human beings who need protection in the form of adults’ intervention because a criminal imposition on children does not always have a positive impact on law enforcement itself. This is because the children's futures can still be improved and their rights are human rights. The best interests of the children should be the main consideration.